Regional marketing (Caribbean Tourism Organization BridgetownBB, 1995)
Looks briefly at the Caribbean Coalition for Tourism Regional Marketing Programme as it applies to North America. Examines the performance of the Caribbean Regional advertising and Marketing Program for the period 1992-1995.
DC